If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+5)-2(3+x)-6x=13-4(2x+1)
We move all terms to the left:
3(2x+5)-2(3+x)-6x-(13-4(2x+1))=0
We add all the numbers together, and all the variables
3(2x+5)-2(x+3)-6x-(13-4(2x+1))=0
We add all the numbers together, and all the variables
-6x+3(2x+5)-2(x+3)-(13-4(2x+1))=0
We multiply parentheses
-6x+6x-2x-(13-4(2x+1))+15-6=0
We calculate terms in parentheses: -(13-4(2x+1)), so:We add all the numbers together, and all the variables
13-4(2x+1)
determiningTheFunctionDomain -4(2x+1)+13
We multiply parentheses
-8x-4+13
We add all the numbers together, and all the variables
-8x+9
Back to the equation:
-(-8x+9)
-2x-(-8x+9)+9=0
We get rid of parentheses
-2x+8x-9+9=0
We add all the numbers together, and all the variables
6x=0
x=0/6
x=0
| 35+15x=65 | | 4x-8+2x=4x | | (x-2)^2=(x+2)(x-2)+2(1-x) | | 7n+3=3n+277n+3=3n+27 | | 11c+21=37 | | 5(4(-2)+(-7)+x)+x(6-7)=5(-2x)+3 | | 11c-21=37 | | 8x-4+10x-6=180 | | -6(2t+1)=-18 | | 127,5-m=120,5 | | 7(4s+9)=427 | | x/2+3x(x-1)=38 | | 3x12-10x-5=10 | | 2(x-4)=4(3+x) | | n+11,2=100 | | 4+12x-6(3x-2)+13=11+4(3-2x) | | 2x+19=115 | | 5(6+x)+3(x+4)=2(x+6) | | y/5=1005 | | 34+x2-45-12=43x+2 | | 3xx=48,3 | | 4(x-3)=9x+54 | | -(x+2)+3(x+2)=4-(x-1) | | 4x-10=9x-14 | | -2x-53=-6x+56 | | 7(x-2)+2x=3(x-8)+x-5 | | 12x-7=5x+133 | | 4x+7+6x=12+5x-25 | | X(2x-1)^2-x(2x-1)(2x+1)=0 | | 3/2x-5=7/3 | | 2x+3x+8=6x+5 | | -8x=+16 |